2010
DOI: 10.1086/655396
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of Panton‐Valentine Leukocidin (PVL), PVL Isoforms, and Clonal Complex in theStaphylococcus aureusPopulation of Northern Australia

Abstract: PVL(+) and PVL(-) infections are clearly distinct. MSSA contributes a large but underrecognized burden of PVL(+) disease. Compared with elsewhere in the world, there is a relative abundance of the clade that contains CC93 and CC121 in both northern Australia and Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
55
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 44 publications
10
55
1
1
Order By: Relevance
“…Less than 10% of the S. aureus HAP isolates in this study contained pvl. This relatively low prevalence stands in sharp contrast to trends seen in soft tissue infections (1,45) as well as in a pneumonia study in children (6).…”
Section: Discussioncontrasting
confidence: 76%
“…Less than 10% of the S. aureus HAP isolates in this study contained pvl. This relatively low prevalence stands in sharp contrast to trends seen in soft tissue infections (1,45) as well as in a pneumonia study in children (6).…”
Section: Discussioncontrasting
confidence: 76%
“…These strains are genetically similar in susceptibility and toxin profile, as well as spa type, to the recently described ST22 PVL-MRSA United Kingdom strains, rather than the predominant hospital-acquired MRSA (HA-MRSA) ST22 EMRSA-15 clone (5). This study observed the previously noted geographical and clonal bias in the distribution of the PVL haplotypes, with the R haplotype limited to a few lineages, predominantly in the United States and more recently Australia (22,29). Due to previous reports of R haplotypes being found in the United Kingdom in significant numbers of MRSA strains (4,24), the dearth of R haplotypes in this small study population may reflect more on the methicillin susceptibility of the isolates rather than geographical location.…”
mentioning
confidence: 49%
“…Represented among the MSSA isolates in this study were major sequence types (ST22, ST88, ST30, and ST1) associated with PVL-MRSA clones (21,27,29). Though the majority of PVL-MRSA clones circulating in the United Kingdom belong to either ST8, ST30, or ST80 (13, 17, 23), the predominant group described in this study, ST22, also constitute a significant burden of infection (13).…”
mentioning
confidence: 59%
See 2 more Smart Citations